1971
DOI: 10.2134/agronj1971.00021962006300010037x
|View full text |Cite
|
Sign up to set email alerts
|

Corn Yields with Fall, Spring, and Sidedress Nitrogen1

Abstract: Studies in central and northern Illinois at 4 locations and 12 location‐years were conducted with 5 rates of N applied in the fall and as spring‐preplant. Sidedress N was also included at 1 of the 4 locations for 4 years. Relative efficiency of the times of application was calculated by dividing the corn (Zea mays L.) yield increase from a given rate of N added at one time by the yield increase from the same rate of N applied at another time. At the Carthage and Hartsburg locations the 3‐year average relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
2
2

Year Published

1993
1993
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 1 publication
4
70
2
2
Order By: Relevance
“…Therefore, more N fertilizer (around 60-70% of the total N fertilizer applied) should be applied during the fastest growing stages of the crop to achieve synchrony between the N supply and crop demand. This is consistent with early observations that N fertilizer should be applied close to the peak N uptake to increase grain yield and NUE and decrease the opportunity for soil N losses (Russelle et al 1981;Welch et al 1971).…”
Section: Spatially and Temporally Matching The Rhizospheric Nitrogen supporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, more N fertilizer (around 60-70% of the total N fertilizer applied) should be applied during the fastest growing stages of the crop to achieve synchrony between the N supply and crop demand. This is consistent with early observations that N fertilizer should be applied close to the peak N uptake to increase grain yield and NUE and decrease the opportunity for soil N losses (Russelle et al 1981;Welch et al 1971).…”
Section: Spatially and Temporally Matching The Rhizospheric Nitrogen supporting
confidence: 92%
“…Nitrogen application in excess of crop N demand at the early growth stage increases the potential for nitrate-N leaching and results in excessive crop growth that is more susceptible to disease infection and wheat lodging. Applying N fertilizer near to the time it is needed by the crop increases crop grain yield and improves NUE (Russelle et al 1981;Welch et al 1971). Results from Iowa (Sanchez and Blackmer 1988) indicate that 50-64% of fall-applied N is lost from the upper 1.5 m of soil by processes other than crop uptake.…”
Section: Ignorance Of N Contributed By the Soil And Environmentmentioning
confidence: 99%
“…Efficiency of use from a single pre-plant N-fertilizer application typically decreases in proportion to the amount of N fertilizer applied (Reddy and Reddy, 1993). Other studies have substantiated that in-season applied N resulted in a higher NUE than when N is pre-plant applied (Miller et al, 1975;Olson et al, 1986;Welch et al, 1971;Randall et al, 2003a,b). Collectively, these results agree with the recommendations of Keeney (1982), who advocated that the most logical approach to increasing NUE is to supply N as it is needed by the crop.…”
Section: Causes Of Low Nue For Current N Management Strategiesmentioning
confidence: 99%
“…It is not surprising that tile nitrate yields were greater from the C-C system than the C-S system because no fertilizer was applied during the soybean year in C-S in 2011. However, numerous studies have shown that fall and winter applications of fertilizer N can lead to increased tile nitrate losses compared with spring applications (Welch et al, 1971;Frye, 1977;Gentry et al, 1998;Randall et al, 2003;Clover, 2005). After corn in 2010, nitrate concentration in both tiles tracked one another until a large precipitation and tile flow event on 16 Feb. 2011.…”
Section: Fertilizer Timingmentioning
confidence: 99%